2021
DOI: 10.18535/ijsrm/v9i1.em02
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Job Autonomy, Organizational Learning, and Work Environment on Organizational Commitment of Public Sector Employees in the Ashanti Region of Ghana

Abstract: Many employers and researchers across the globe have, over the years, adopted different approaches that can ensure employees' commitment to an organization. In this study, we seek to find a linkage between Job Autonomy, Organizational Learning, and Work Environment towards Organizational Commitment of public sector employees in Ghana. Data were obtained from three hundred and thirty (330) employees of five (5) Metropolitan, Municipal and Districts Assemblies (MMDAs) in the Ashanti Region of Ghana through the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Table 3 showcases the various constructs' collinearity values, evaluated by a variance inflation factor (VIF) to assess collinearity issues. Evaluations revealed no collinearity problems in the model (Ahakwa et al, 2021), as VIF values for all constructs were below the threshold of 5 (Kim, 2019). The degree to which measures are not a duplication of other variables constitutes discriminant validity.…”
Section: Evaluation Of the Measurement Modelmentioning
confidence: 85%
“…Table 3 showcases the various constructs' collinearity values, evaluated by a variance inflation factor (VIF) to assess collinearity issues. Evaluations revealed no collinearity problems in the model (Ahakwa et al, 2021), as VIF values for all constructs were below the threshold of 5 (Kim, 2019). The degree to which measures are not a duplication of other variables constitutes discriminant validity.…”
Section: Evaluation Of the Measurement Modelmentioning
confidence: 85%
“…Kim (2019) proposed that if the VIF values are more than 5, there is a collinearity problem with the model, whereas VIF values less than five mean there is no collinearity problem with the model. From Table 3, it is evidenced that all the values of the VIF assessment are lesser than the threshold value signifying that the model has no collinearity problems, supporting those of Ahakwa et al (2021a) and Odai et al (2021). Also, the occurrence of a VIF greater than 3.3 is proposed as an indication of pathological collinearity and indicates that the model may be contaminated by CMB.…”
Section: Measurement Model Assessmentmentioning
confidence: 89%
“…It is undoubtedly very required for all establishments to cultivate OC since personnel is the key foundation of sustained achievement and efficiency. "OC is described as an emotional attitude that binds personnel to an establishment in a way that decreases turnover intention" (Ahakwa, Yang, Agba Tackie, et al, 2021). Lee, Ashford, Walsh, and Mowday (1992) proposed the most generally accepted definition for OC as "the level to which a person's participation in his organization."…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…The authors added that loyalty is demonstrated by an employee's ability to labor successfully in an establishment and the desire to sustain the relationship devoid of attempting to turn to another (Lee et al, 1992). Organizations with greatly committed personnel, since it's widely agreed that OC might lead to countless organizational results; reduced turnover, greater motivation level, enriched citizenship conduct, and continuous organizational support (Ahakwa, Yang, Agba Tackie, et al, 2021). "The commitment of workers is a sign of greater devotion and improved efficiency" (Porter, Steers, Mowday, & Boulian, 1974).…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation